2022
DOI: 10.3389/fneur.2022.880661
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postischemic Stroke Epilepsy in Young Adults: A Nationwide Population-Based Study in Taiwan

Abstract: BackgroundThe incidence of ischemic stroke has been increasing in the young population over the past 20 years. Poststroke epilepsy (PSE) is a common complication after stroke. However, few population-based studies with sufficient follow-up have investigated factors associated with PSE, especially factors related to comorbidities and unhealthy lifestyles in the modern young population. Accordingly, this study aimed to determine the long-term incidence and these risk factors for PSE young adults.MethodsThis coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…It occurred twice that two articles reported on the same cohort (Hordaland County cohort Norway 21,22 and Sahlgrenska Academy Study on Ischemic Stroke Sweden), 23,24 but provided different information; thus, we included both. More than half of the studies (16/29) included a population of ischemic stroke only [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] (Table 1). Time since stroke while evaluating cognitive outcomes ranged from a few hours to 11 years, but almost half of the studies (13/29) reported on people in the chronic phase [21][22][23][24]26,28,30,31,36,[38][39][40][41] and the other half (14/29) included people in the non-chronic phase.…”
Section: Included Articlesmentioning
confidence: 99%
“…It occurred twice that two articles reported on the same cohort (Hordaland County cohort Norway 21,22 and Sahlgrenska Academy Study on Ischemic Stroke Sweden), 23,24 but provided different information; thus, we included both. More than half of the studies (16/29) included a population of ischemic stroke only [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] (Table 1). Time since stroke while evaluating cognitive outcomes ranged from a few hours to 11 years, but almost half of the studies (13/29) reported on people in the chronic phase [21][22][23][24]26,28,30,31,36,[38][39][40][41] and the other half (14/29) included people in the non-chronic phase.…”
Section: Included Articlesmentioning
confidence: 99%
“…Five studies (7.0%) had a high risk of bias, 35 studies (49.3%) presented a moderate risk of bias, and 31 studies (43.7%) had a low risk of bias (eTable 4 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analyses were appropriate in 44 studies (62%) . Confounding factors were identified in 58 studies (81.7%) and were adjusted in the statistical analysis in 53 studies (74.6%) . Only 37 studies (52.1%) provided complete follow-up data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations